Thermal behavior of indirect solar dryer: Nocturnal usage of solar air collector with PCM. (1st April 2017) - El Khadraoui, Aymen; Bouadila, Salwa; Kooli, Sami; Farhat, Abdelhamid; Guizani, Amenallah
Abstract: An indirect type forced convection solar dryer using Phase Change Material (PCM) was designed, constructed and experimentally investigated. The dryer consists of a solar air panel for a direct heating of the drying agent, a solar energy accumulator (solar air collector with PCM cavity) and a drying chamber. The solar dryer was tested under no load with and without PCM. The present study is aimed at investigating the feasibility of using a solar air heater with PCM to store the solar energy during the daytime, and to release it during the night. Experiments were conducted to evaluate the charging and the discharging characteristics of the latent storage unit (PCM cavity). The daily energy efficiency of the solar energy accumulator reached 33.9%, while the daily exergy efficiency reached 8.5%. The results show that after using the solar energy accumulator, the temperature of the drying chamber is higher than the ambient temperature by 4–16 °C, all the night. In addition, the relative humidity in the drying chamber was observed 17–34.5% lower than the ambient relative humidity, in the case of the solar dyer with PCM. Highlights: A new indirect solar dryer: nocturnal use of a solar air heater with phase change materials. Experimental study of the indirect solar dryer with and without phase change materials. Energy and exergy analysis of the solar air heater with latent storage.